Model of Internalization of Religious Moderation Values through Muthala’ah Learning Arabic Language Education Study Program, UIN Datokarama Palu - Ubadah Ubadah; Agustan Agustan; Muhammad Gazali; Muhammad Nur Asmawi (Institut Agama Islam Negeri Curup, 2026)
This study investigates the internalization of values of religious moderation through the Muthala’ah course in the Arabic Language Education Study Program at UIN Datokarama Palu. Specifically, it explores the patterns and strategies employed, the core values emphasized, and the obstacles and possible solutions in the internalization process. Adopting a qualitative design, data were collected through observation, interviews, and documentation, and were analyzed thematically. The findings indicate that internalization is implemented through a structured process comprising instructional planning (syllabus and lesson plan development), the integration of moderation-themed texts into classroom activities, and a combined grammatical and semantic analysis of the texts. The values primarily internalized include al-tawassuth (moderation), al-i’tidal (fairness), al-tasamuh (tolerance), and national commitment (muwathanah). However, the process faces several challenges, such as lecturers’ continued reliance on purely textual approaches, difficulties in packaging moderation-oriented materials, and limited specialized learning resources. The study concludes that the Muthala’ah course has strong potential as a pedagogical medium for fostering moderate and tolerant students, provided that lecturers deliberately integrate value-oriented content with linguistic analysis in their instructional design.